2020
DOI: 10.1002/agj2.20451
|View full text |Cite
|
Sign up to set email alerts
|

Endangerment of Ostrya rehderiana Chun and its relationship with rhizosphere soil microflora

Abstract: Ostrya rehderiana Chun (Or) is an endangered plant in China. The rhizosphere microbial community is one of the key factors influencing the growth and development of plants. Soil samples in the rhizosphere of wild Or (W_Or), cultivated Or (C_Or) and the predominant plant species Cryptomeria fortunei Hooibrenk ex Otto et Diet (CfH) all growing in the same habitat were investigated. We performed polymerase chain reaction (PCR) in 16S rDNA region for bacteria and internal transcribed spacer (ITS) rDNA regions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…As reported previously, the lignin content is higher in the root than in stems and leaves and increases with maize growth . Moreover, it is the primary contributor to soil lignin, and some species of fungi can degrade lignin; also, some bacteria have a similar effect but are not yet elucidated . Supposedly, the growth-promoting effect of the biostimulant in our study is partially dependent on phenylpropanoid biosynthesis and subsequent lignin production.…”
Section: Discussionsupporting
confidence: 71%
“…As reported previously, the lignin content is higher in the root than in stems and leaves and increases with maize growth . Moreover, it is the primary contributor to soil lignin, and some species of fungi can degrade lignin; also, some bacteria have a similar effect but are not yet elucidated . Supposedly, the growth-promoting effect of the biostimulant in our study is partially dependent on phenylpropanoid biosynthesis and subsequent lignin production.…”
Section: Discussionsupporting
confidence: 71%
“…Tong et al. (2020) studied the relationships between the endangered Ostrya rehderiana Chun and the soil rhizosphere microflora and found that the absence of some essential strains cause the retardation of growth and development of the species. Biomass dynamics with succession in the tropical broad‐leaf evergreen forests was studied by Zeng et al.…”
Section: Resultsmentioning
confidence: 99%
“…Wei et al (2020) studied the soil respiration using four cultivars of Stylo-grass [Stylosanthes guianensis (Aubl.) Sw.] and identifies the main limiting factor for soil health is soil respiration.Jiang, Jin et al (2020) discussed techniques that increase breeding efficiency of maize (Zea mays L.) Tong et al (2020). studied the relationships between the endangered Ostrya rehderiana Chun and the soil rhizosphere microflora and found that the absence of some essential strains cause the retardation of growth and development of the species.…”
mentioning
confidence: 99%
“…Some alternative fungi were also closely associated with CP2_LI09 cohort, e.g., Sporobolomyces and Fusicolla . Sporobolomyces could accumulate beneficial metabolites ( 46 ), while Fusicolla was found as a fungus of soil origin ( 47 ).…”
Section: Discussionmentioning
confidence: 99%